Breaking the Habit: On the Highly Habitualized Nature of Meat Consumption and Implementation Intentions as One Effective Way of Reducing It - Rees, Jonas H.; Bamberg, Sebastian; Jäger, Andreas; Victor, Lennart; Bergmeyer, Minja; Friese, Malte (Basic and applied social psychology, 2018)
Reducing meat consumption is an important element of an effective climate protection strategy, but meat consumption is highly habitualized and therefore difficult to change. This article uses an extended version of the theory of planned behavior with habit strength as additional predictor. In one longitudinal (N = 227) and one prospective correlational study (N = 212), attitudes toward and perceived ease of meat consumption reduction explained about 60% of variance of meat consumption reduction intentions, with habit strength being the strongest correlate of actual self-reported meat consumption. A third experimental study (N = 192) demonstrated that implementation intentions can be an effective strategy for realizing reduction aims. We discuss the central role of habits for meat consumption.